2015
DOI: 10.1039/c5sc01427a
|View full text |Cite
|
Sign up to set email alerts
|

Wide bandgap OPV polymers based on pyridinonedithiophene unit with efficiency >5%

Abstract: We report the properties of a new series of wide band gap photovoltaic polymers based on the N-alkyl 2-pyridone dithiophene (PDT) unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Yu et al reported a novel series of WBG conjugated polymers based on the N‐alkyl 2‐pyridone dithiophene unit, which were developed from their previous investigations on fused amide‐linked systems to create the thieno[2′,3′:5′,6′]pyrido[3,4‐g]thieno[3,2‐c]isoquinoline‐5,11(4H,10H)‐dione (TPTI) monomer ( P43 ‐ P47 ). The best performance of this type of donor was achieved from the P47 :PC 71 BM blend, with a PCE of 5.33% presented . The dithienosilole (DTS)‐thiazolothiazole‐based D‐A copolymer PSEHTT ( P48 ) presented a wide bandgap of 1.82 eV; the photovoltaic properties of P48 were investigated in an ITO/PEDOT/ P48 :PC 71 BM/LiF/Al structure.…”
Section: Wbg Copolymersmentioning
confidence: 99%
“…Yu et al reported a novel series of WBG conjugated polymers based on the N‐alkyl 2‐pyridone dithiophene unit, which were developed from their previous investigations on fused amide‐linked systems to create the thieno[2′,3′:5′,6′]pyrido[3,4‐g]thieno[3,2‐c]isoquinoline‐5,11(4H,10H)‐dione (TPTI) monomer ( P43 ‐ P47 ). The best performance of this type of donor was achieved from the P47 :PC 71 BM blend, with a PCE of 5.33% presented . The dithienosilole (DTS)‐thiazolothiazole‐based D‐A copolymer PSEHTT ( P48 ) presented a wide bandgap of 1.82 eV; the photovoltaic properties of P48 were investigated in an ITO/PEDOT/ P48 :PC 71 BM/LiF/Al structure.…”
Section: Wbg Copolymersmentioning
confidence: 99%
“…Rational design of D and A units could produce high‐performance D–A copolymers . Among the acceptor units, polycyclic aromatic lactams (PALs) demonstrated great potential in developing efficient D–A copolymers . Benefiting from their strong electron‐withdrawing capability and good planarity, PAL‐based D–A copolymers usually exhibit deep HOMO levels and high hole mobilities.…”
Section: Optical and Electrochemical Data For The Polymersmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] To tune the optical and electrical properties of the available active materials, new chemical motifs incorporating fused rings and alternating donor-acceptor (D-A) structures in the polymer chain have been designed and synthesized. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Benzothiadiazole (BT) and its analogs have been used as electron acceptor groups in conjunction with various donor units such as cyclopentadithiophene (CPDT); compounds containing these acceptor groups exhibit lower-energy levels and a reduction in the band gap compared with other D-A alternating copolymers. [23][24][25][26][27][28][29] Since the development of poly [4,4- Figure 1), one of the first efficient third-generation donor-type conjugated polymers, …”
Section: Introductionmentioning
confidence: 99%